Coda Wave Interferometry for Accurate Simultaneous Monitoring of Velocity and Acoustic Source Locations in Experimental Rock Physics. Issue 6 (26th June 2019) - Singh, J.; Curtis, A.; Zhao, Y.; Cartwright‐Taylor, A.; Main, I.
Abstract: In many geoscientific, material science, and engineering applications it is of importance to estimate a representative bulk seismic velocity of materials or to locate the source of recorded seismic or acoustic waves. Such estimates are necessary in order to interpret industrial seismic and earthquake seismological data, for example, in nondestructive evaluation and monitoring of structural materials, and as an input to rock physics models that predict other parameters of interest. Bulk velocity is commonly estimated in laboratories from the time of flight of the first‐arriving wave between a source and a receiver, assuming a linear raypath. In heterogeneous media, that method provides biased estimates of the bulk velocity, and of derived parameters such as temporal velocity changes or the locations of acoustic emissions. We show that coda wave interferometry (CWI) characterizes changes in the bulk properties of scattering media far more effectively on the scale of laboratory rock samples. Compared to conventional methods, CWI provides significant improvements in both accuracy and precision of estimates of velocity changes, and distances between pairs of acoustic sources, remaining accurate in the presence of background noise, and when source location and velocity perturbations occur simultaneously. CWI also allows 3‐D relative locations of clusters of acoustic emissions to be estimated using only a single sensor. We present a method to use CWI to infer changes in both P and S wave velocities individually. These innovations represent significant improvements in our ability to characterize the evolution of properties of media for a variety of applications. Key Points: Conventional methods for measuring changes in seismic velocity and source locations may be inaccurate, especially in a high‐frequency regime CWI provides far greater accuracy in estimating changes in velocity and between source locations, even with high background noise levels A new method is presented to infer both P and S wave average velocity changes from coda wave interferometry